2020
DOI: 10.1002/cctc.202000032
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Palladium(0)‐Allyl Interactions in the Tsuji‐Trost Reaction, derived from Single‐Molecule Fluorescence Microscopy

Abstract: Single-molecule (SM) chemistry is devoted to unravel reaction steps which are hidden in cuvette experiments. Controversies about the substrate activation during the Tsuji-Trost deallylation motivated us to study, on the single-molecule level, the kinetics of the catalyst precursor Pd(PPh 3 ) 4 with our recently designed two-color fluorescent probes. Photochemical, metal-free bypass reactions were found and taken into account by the combina-tion of spectrally separated single-molecule TIRF-microscopy and state-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…In previous work, we have established pyrene-based superphotoacids with estimated p K a * values down to −4 in the excited state, high photostability, and high fluorescence quantum yields . They proved to be versatile probes for single-molecule microscopy , and time-resolved spectroscopy. , The focus is now placed on the elementary proton transfer step, that is, the formation of the HBIP: How does the surrounding solvent influence the PT process?…”
mentioning
confidence: 99%
“…In previous work, we have established pyrene-based superphotoacids with estimated p K a * values down to −4 in the excited state, high photostability, and high fluorescence quantum yields . They proved to be versatile probes for single-molecule microscopy , and time-resolved spectroscopy. , The focus is now placed on the elementary proton transfer step, that is, the formation of the HBIP: How does the surrounding solvent influence the PT process?…”
mentioning
confidence: 99%
“…Although subensemble fluorescence microscopy techniques have been employed to explore mechanisms in aqueous biological systems since the 1980s [1], the adaptation to study chemical reactions was not straightforward and many challenges had to be overcome [2]. For example, chemists had to translate microscopy techniques to achieve compatibility with the organic solvents [3] and air-free techniques that are often critical for studying organic and organometallic reactions [4,5]. Equally important to these technical barriers, an initial lack of realization of shared scientific interests between single-molecule/-particle microscopy experts and synthetic/mechanistic chemists contributed to the relatively late blooming of the field.…”
Section: A Unique Tool For Exploring Chemical Reactionsmentioning
confidence: 99%
“…Furthermore, two-color single-molecule experiments investigated the selectivity of single molecular Grubbs catalysts for chain-elongation or chain-termination reactions; these experiments concluded that the selectivity of catalysts for these competing reactions varies with time [43]. In palladium catalysis, Goldsmith investigated the initiation-step kinetics of an immobilized pyridine-palladium-NHC ('PEPPSI' type) catalyst [44], while Jung studied the palladium-catalyzed Tsuji-Trost deallylation mechanism and discovered that the mechanism involves the formation of a π complex and that it proceeds through a long-lived Pd(II) intermediate [5,45].…”
Section: Highlightsmentioning
confidence: 99%
See 1 more Smart Citation
“…These traditional measurement techniques, however, are incapable of measuring polymer behavior at the single-molecule and -particle level. In contrast, at the other end of the analytical regime, single-molecule/particle techniques can provide information on tethered or otherwise restricted polymer behaviors in real time with high spatial resolution, but to date cannot measure behavior in freely diffusing solution at time scales beyond millisecond-scale snapshots or provide a way to see changes in the same species over time, leaving the solution behavior of growing polymers at the single-particle level unknown. Therefore, an analytical trade-off has existed up to this point: measure in freely diffusing solution and only acquire ensemble data or measure restricted-diffusion species and reveal single-particle/molecule data.…”
Section: Introductionmentioning
confidence: 99%